High-strength high-storage-stability temperature-sensitive phase-change reversible hydrogel and preparation method thereof

A thermosensitive phase-change reversible hydrogel with improved phase transition temperature and stability is achieved using poly(N-isopropylacrylamide), gelatin-grafted gallic acid, and polyvinyl alcohol, addressing the limitations of existing hydrogels in medical and cosmetic fields.

CN119241871AActive Publication Date: 2025-01-03FUZHOU UNIV

Patent Information

Application Number
CN202411635259.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-03
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

Existing hydrogels suffer from low phase transition temperature, poor storage stability, and low mechanical strength, which limits their application in medical and cosmetic fields due to difficulties in injection and degradation.

Method used

A high-strength, high-storage-stability thermosensitive phase-change reversible hydrogel is prepared using poly(N-isopropylacrylamide) as a matrix, gelatin-grafted gallic acid as an entanglement agent, and polyvinyl alcohol as a destructurant, with a simple low-temperature stirring process.

Benefits of technology

The hydrogel exhibits a high phase transition temperature of 32-33°C, excellent mechanical properties, thermosensitive phase transition reversibility, and degradability, with a storage stability of over 365 days, making it suitable for medical and cosmetic applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241871A_ABST
    Figure CN119241871A_ABST
Patent Text Reader

Abstract

The invention discloses high-strength high-storage-stability temperature-sensitive phase-change reversible hydrogel and a preparation method thereof, and belongs to the technical field of preparation of hydrogel. The temperature-sensitive phase-change reversible hydrogel with high strength and high storage stability is prepared by taking poly (N-isopropylacrylamide) as a matrix, gelatin grafted gallic acid as an entanglement agent, polyvinyl alcohol as a deconstruction agent and deionized water as a solvent through low-temperature stirring. The hydrogel prepared by the invention has higher phase change temperature and storage stability, better mechanical properties, excellent biocompatibility, temperature-sensitive phase change property and temperature-sensitive phase change reversibility, is non-toxic, injectable and degradable, is simple in preparation method, is mainly used in the fields of medical treatment and cosmetology, and has remarkable economic value and social benefit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogel preparation, and specifically relates to a high-strength, high-storage stability, temperature-sensitive phase-change reversible hydrogel and a preparation method thereof. Background Art

[0002] Hydrogels have become excellent drug carrier materials due to their diverse preparation methods, adjustable components, biocompatibility and other characteristics, and are widely used in the medical and cosmetic fields. However, hydrogels need to have certain mechanical properties when used, so the hydrogels currently widely used are mainly solid hydrogels. When patients receive treatment, solid hydrogels loaded with biological factors or drugs are injected into the human body through a needle. On the one hand, the large viscosity of solid hydrogels will seriously affect the uniformity of the dispersion of biological factors or drugs in the hydrogel carrier. On the other hand, the large viscosity of solid hydrogels makes it difficult to inject into the human body through usually thinner needles, and only thicker needles can be used to inject solid hydrogels, which will result in a larger wound surface during the drug administration process and increase the patient's pain. Patent CN117467159 A is an injectable medical thermosensitive hydrogel and its preparation method. N-isopropylacrylamide is used as a monomer and azobisisobutylamidine hydrochloride is used as an initiator. Poly-N-isopropylacrylamide is prepared by free radical polymerization. After dialysis and impurity removal, it is mixed with polyvinyl alcohol and gallic acid, and the injectable medical thermosensitive hydrogel is prepared by low-temperature stirring. Although the above hydrogel has certain mechanical properties, excellent biocompatibility, thermosensitive phase change and thermosensitive phase change reversibility, the phase change temperature of the above hydrogel is only 12~13℃, and it needs to be stored at low temperature, and the storage stability is poor. At the same time, the maximum storage modulus of the above hydrogel is only 198~200 Pa, and the strength is relatively low, which seriously affects the wide application of the above hydrogel.

[0003] In the patent CN118576748A, a preparation method and application of an adhesive and antibacterial wound dressing gel, and the patent CN118496523A, a 3D printing hydrogel and its preparation method and application, although there are also research reports on the use of gelatin grafted gallic acid in hydrogels, these technologies usually use chemical catalytic reactions or photochemical reactions to chemically bond gelatin grafted gallic acid with other polymers to form hydrogels. On the one hand, chemical catalytic reactions or photochemical reactions involve complex chemical reaction processes, resulting in a relatively complex process for forming hydrogels. On the other hand, because gelatin grafted gallic acid and other polymers generate stable covalent bonds through chemical catalytic reactions or photocatalytic reactions, the formed hydrogel does not have phase change reversibility and has poor degradability. Summary of the invention

[0004] The present invention aims at the problems of low phase transition temperature, poor storage stability, low strength and the like of hydrogels reported so far, and provides a high-strength and high-storage-stability thermosensitive phase-change reversible hydrogel and a preparation method thereof. The hydrogel prepared by the present invention has high phase transition temperature and storage stability, good mechanical properties, excellent biocompatibility, thermosensitive phase transition and thermosensitive phase transition reversibility, and is non-toxic, injectable, degradable, and has a simple preparation method. It is mainly used in the medical and beauty fields and has significant economic value and social benefits.

[0005] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a high-strength, high-storage-stability thermosensitive phase-change reversible hydrogel, which uses poly (N-isopropylacrylamide) as a matrix, gelatin-grafted gallic acid as an entanglement agent, polyvinyl alcohol as a destructurant, and deionized water as a solvent, and obtains the high-strength, high-storage-stability thermosensitive phase-change reversible hydrogel by low-temperature stirring.

[0006] The method for preparing the high-strength and high-storage-stability thermosensitive phase-change reversible hydrogel comprises the following steps: (1) Add 2-10 g of gelatin to 100-300 mL of deionized water, and stir mechanically at 30-60 °C for 10-30 min to obtain a gelatin solution. Then, add a mixture of gallic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide to a mixed solution of 100-300 mL of N,N-dimethylformamide and deionized water, and stir mechanically at room temperature for 30-60 min to obtain a gallic acid mixed solution. Finally, add the gallic acid mixed solution dropwise to the gelatin solution, and stir mechanically at 30-50 °C for 6-18 h. The reaction mixture is dialyzed, filtered, and freeze-dried to obtain gelatin grafted with gallic acid. (2) 3-12 g of poly (N-isopropylacrylamide) was added to 40-100 mL of deionized water, and the mixture was mechanically stirred at 10-25 °C for 20-40 min to obtain a poly (N-isopropylacrylamide) solution. Then, 1-3 g of gelatin grafted gallic acid and 0.4-0.8 g of poly (vinyl alcohol) were added to 20-100 mL of deionized water, and the mixture was mechanically stirred at 60-100 °C for 30-60 min, and then at 10-25 °C for 20-40 min to obtain a mixed solution of gelatin grafted gallic acid and poly (vinyl alcohol). Finally, the mixed solution of gelatin grafted gallic acid and poly (vinyl alcohol) was added dropwise to the poly (N-isopropylacrylamide) solution, and the mixture was mechanically stirred at 10-25 °C for 20-40 min, and then at 10-15 °C for 10-20 min to obtain the high-strength and high-storage-stability thermosensitive phase-change reversible hydrogel.

[0007] Furthermore, in step (1), the relative molecular mass of the gelatin is 10000-100000; the mass ratio of the gelatin to gallic acid is 2:1-4:1; the mass ratio of the mixture of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide to gallic acid is 1:1-1.5:1; and the molar ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide to N-hydroxysuccinimide is 1:2.

[0008] Furthermore, in step (1), the volume ratio of N,N-dimethylformamide to deionized water is 1:2 to 1:4.

[0009] Furthermore, the dialysis temperature in step (1) is 25-35°C, the time is 7-14 days, the molecular weight cut-off is 3500 Da, and the dialysate is deionized water.

[0010] Furthermore, the relative molecular mass of the polyvinyl alcohol in step (2) is 10,000-100,000.

[0011] A high-strength and high-storage stability thermosensitive phase-change reversible hydrogel prepared by the above method, wherein the phase change temperature of the hydrogel is 32~33°C, the storage modulus at 37°C is 542~548 Pa, the composite viscosity at 5°C is 1.62~1.73 Pa·s, the composite viscosity at 37°C is 78.5~79.6 Pa·s, the storage validity period is greater than 365 days, and the weight loss rate is 68.4~71.7%.

[0012] The beneficial effects of the present invention are: (1) The present invention uses poly (N-isopropylacrylamide) as a matrix, gelatin grafted gallic acid as an entanglement agent, and polyvinyl alcohol as a destructurant, and the above three polymers are uniformly mixed by mechanical stirring. When the temperature is lower than the phase transition temperature, the hydrophilic effect of poly (N-isopropylacrylamide) dominated by the amide group is stronger than the hydrophobic effect dominated by the isopropyl group, and the molecular chain segments are stretched and stably dissolved in deionized water. At the same time, through the hydrogen bonding between gelatin grafted gallic acid, polyvinyl alcohol and poly (N-isopropylacrylamide), gelatin grafted gallic acid and polyvinyl alcohol can also be stably dissolved in deionized water. At this time, the three polymers form a transparent liquid hydrogel with very low gel strength. When the temperature is higher than the phase transition temperature, the hydrophobic effect of poly N-isopropylacrylamide dominated by isopropyl is stronger than the hydrophilic effect dominated by amide, the molecular chain segments curl, and at the same time, through the hydrogen bonding between gelatin grafted gallic acid, polyvinyl alcohol and poly N-isopropylacrylamide, gelatin grafted gallic acid, polyvinyl alcohol and poly N-isopropylacrylamide form a stable entangled structure, and the three polymers form a white solid hydrogel. Because the molecular weight of gallic acid is much lower than that of gelatin, the entanglement effect of gelatin grafted gallic acid, polyvinyl alcohol and poly N-isopropylacrylamide is stronger than the entanglement effect of gallic acid, polyvinyl alcohol and poly N-isopropylacrylamide, so when the temperature is higher than the phase transition temperature, the hydrogel prepared by the present invention has a higher strength.

[0013] (2) The present invention uses gelatin grafted with gallic acid as a entanglement agent. Because gelatin grafted with gallic acid has good compatibility with poly (N-isopropylacrylamide), when the temperature is lower than the phase transition temperature, the stability of the transparent liquid hydrogel can be greatly improved through the hydrogen bonding between gelatin grafted with gallic acid and poly (N-isopropylacrylamide). And because the molecular weight of gelatin is much higher than that of gallic acid, when the temperature rises, the hydrogen bonding between gelatin grafted with gallic acid and poly (N-isopropylacrylamide) limits the curling of the molecular chain segments of poly (N-isopropylacrylamide), so the hydrogel prepared by the present invention has a higher phase transition temperature. In addition, since gelatin and poly (N-isopropylacrylamide) have poor compatibility, if gelatin is directly mixed with poly (N-isopropylacrylamide) and polyvinyl alcohol, gelatin and poly (N-isopropylacrylamide) will be delaminated. Therefore, the present invention grafts gallic acid onto the gelatin molecular chain, mainly to improve the compatibility of gelatin and poly (N-isopropylacrylamide).

[0014] (3) The present invention utilizes the hydrogen bonding between gelatin grafted gallic acid, polyvinyl alcohol and poly (N-isopropylacrylamide) to form a white solid hydrogel, so the hydrogel has excellent thermosensitive phase change reversibility. At the same time, because there is no chemical bonding between gelatin grafted gallic acid, polyvinyl alcohol and poly (N-isopropylacrylamide), the rapid degradation of gelatin grafted gallic acid in the body will cause the white solid hydrogel to decompose rapidly, and the hydrogel has excellent degradability.

[0015] (4) The polyvinyl alcohol of the present invention mainly plays the role of deconstructing the curled molecular chain of poly (N-isopropylacrylamide). The hydroxyl density of the polyvinyl alcohol molecular chain is high. As the temperature decreases, the hydrophobic effect of poly (N-isopropylacrylamide) decreases rapidly and the hydrophilic effect increases rapidly. Therefore, polyvinyl alcohol can well eliminate the effect of gelatin grafted gallic acid on stabilizing the entanglement of poly (N-isopropylacrylamide). The molecular chain segments of poly (N-isopropylacrylamide) can be transformed into a stretched structure relatively quickly. The gelatin grafted gallic acid, polyvinyl alcohol and poly (N-isopropylacrylamide) are quickly transformed from a white solid hydrogel to a transparent liquid hydrogel, completing the reversible phase transition of the hydrogel.

[0016] (5) The hydrogel prepared by the present invention has a high phase transition temperature and storage stability, good mechanical properties, excellent biocompatibility, thermosensitive phase transition and thermosensitive phase transition reversibility. The phase transition temperature is 32-33 °C, the storage modulus at 37 °C is 542-548 Pa, the composite viscosity at 5 °C is 1.62-1.73 Pa·s, the composite viscosity at 37 °C is 78.5-79.6 Pa·s, the storage validity period is greater than 365 days, the weight loss rate is 68.4-71.7%, and it is non-toxic, injectable, and has a simple preparation method. It is mainly used in the medical and beauty fields and has significant economic value and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of gelatin grafted with gallic acid and gelatin prepared in Example 1.

[0018] Figure 2 This is the infrared absorption spectrum of poly (N-isopropylacrylamide) in Example 1.

[0019] Figure 3 These are morphological pictures of the hydrogel prepared in Example 1 at 18°C ​​(A), when heated to 37°C (B), and when cooled again to 18°C ​​(C).

[0020] Figure 4 The morphology of the hydrogel prepared in Example 1 after being left at 18°C ​​for 365 days (A) and the finished product prepared in Comparative Example 1 after being left at 5°C for 15 days (B).

[0021] Figure 5 The morphology of the finished products obtained in Comparative Example 2 (A) and Comparative Example 3 (B) at 18°C. DETAILED DESCRIPTION

[0022] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0023] Example 1 (1) First, 6 g of gelatin with a relative molecular mass of 50,000 was added to 200 mL of deionized water and mechanically stirred at 45 °C for 20 min to obtain a gelatin solution. Then, 2 g of gallic acid, 2.4 g of a mixture of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide (molar ratio 1:2) were added to 200 mL of a mixed solution of N,N-dimethylformamide and deionized water with a volume ratio of 1:3 and mechanically stirred at room temperature for 45 min to obtain a gallic acid mixed solution. Finally, the gallic acid mixed solution was added dropwise to the gelatin solution and mechanically stirred at 40 °C for 12 h. After the reaction was completed, the reaction solution was poured into a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed against deionized water for 10 days at a dialysis temperature of 30 °C. After the dialysis was completed, the gelatin grafted gallic acid was obtained by filtration and freeze-drying.

[0024] (2) Add 7.5 g of poly (N-isopropylacrylamide) into 70 mL of deionized water and stir mechanically at 18 °C for 30 min to obtain a poly (N-isopropylacrylamide) solution. Then, add 2 g of gelatin grafted gallic acid and 0.6 g of poly (vinyl alcohol) with a relative molecular mass of 50,000 into 60 mL of deionized water and stir mechanically at 80 °C for 45 min and then at 18 °C for 30 min to obtain a mixed solution of gelatin grafted gallic acid and poly (vinyl alcohol). Finally, add the mixed solution of gelatin grafted gallic acid and poly (vinyl alcohol) dropwise into the poly (N-isopropylacrylamide) solution and stir mechanically at 18 °C for 30 min and then stand at 12 °C for 15 min to obtain a hydrogel.

[0025] Figure 1 This is the H NMR spectrum of gelatin grafted with gallic acid prepared in this example. Compared with the H NMR spectrum of gelatin, the H NMR spectrum of gelatin grafted with gallic acid has a new and obvious resonance peak of hydrogen on the benzene ring at a chemical shift of 7.09 ppm, which indicates that gallic acid is successfully bonded to the gelatin molecular chain.

[0026] Figure 2 This is the infrared absorption spectrum of poly (N-isopropylacrylamide) in this example. As shown in the figure, the -1 and 3274 cm -1 The absorption peak at 2976 cm is the NH bond stretching vibration absorption peak. -1 and 2936 cm -1 The absorption peak at 1640 cm-1 is the CH bond stretching vibration absorption peak. -1 and 1547 cm -1The absorption peaks at 1465 cm-1 are the amide C=O absorption peak and the NH bending vibration absorption peak. -1 The absorption peak at 1388 cm -1 and 1371 cm -1 The absorption peak at is the absorption peak formed by the symmetric deformation vibration coupling splitting of the dimethyl group on the isopropyl group, which proves that poly (N-isopropylacrylamide) was successfully synthesized.

[0027] Figure 3 The morphology of the hydrogel prepared in this example at 18°C ​​(A), heated to 37°C (B), and cooled to 18°C ​​(C) again is shown. As shown in the figure, the hydrogel is a transparent liquid at 18°C, and turns into a white solid when heated to 37°C, and turns into a transparent liquid again when cooled to 18°C ​​again, which shows that the hydrogel prepared in the present invention has excellent reversibility of temperature-sensitive phase transition.

[0028] Figure 4 (A) is a morphology of the hydrogel prepared in this example after standing at 18°C ​​for 365 days. As shown in the figure, the hydrogel is still a transparent liquid after standing at 18°C ​​for 365 days, and no stratification or precipitation occurs, which indicates that the hydrogel prepared in the present invention has excellent storage stability.

[0029] Example 2 (1) 2 g of gelatin with a relative molecular mass of 10000 was added to 100 mL of deionized water and mechanically stirred at 30 °C for 30 min to obtain a gelatin solution. Then, 1 g of gallic acid, 1 g of a mixture of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide (molar ratio of 1:2) was added to 100 mL of a mixed solution of N,N-dimethylformamide and deionized water with a volume ratio of 1:2 and mechanically stirred at room temperature for 30 min to obtain a gallic acid mixed solution. Finally, the gallic acid mixed solution was added dropwise to the gelatin solution and mechanically stirred at 30 °C for 18 h. After the reaction was completed, the reaction solution was poured into a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed with deionized water for 14 days at a dialysis temperature of 25 °C. After the dialysis was completed, the gelatin grafted gallic acid was obtained by filtration and freeze-drying.

[0030] (2) Add 3 g of poly (N-isopropylacrylamide) into 40 mL of deionized water and stir mechanically at 10 °C for 40 min to obtain a poly (N-isopropylacrylamide) solution. Then, add 1 g of gelatin grafted gallic acid and 0.4 g of poly (vinyl alcohol) with a relative molecular mass of 10,000 into 20 mL of deionized water and stir mechanically at 60 °C for 60 min and then at 10 °C for 40 min to obtain a mixed solution of gelatin grafted gallic acid and poly (vinyl alcohol). Finally, add the mixed solution of gelatin grafted gallic acid and poly (vinyl alcohol) dropwise into the poly (N-isopropylacrylamide) solution and stir mechanically at 10 °C for 40 min and then let stand at 10 °C for 10 min to obtain a hydrogel.

[0031] Example 3 (1) 10 g of gelatin with a relative molecular mass of 100,000 was added to 300 mL of deionized water and mechanically stirred at 60 °C for 10 min to obtain a gelatin solution. Then, 2.5 g of gallic acid, 3.75 g of a mixture of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide (molar ratio of 1:2) were added to 300 mL of a mixed solution of N,N-dimethylformamide and deionized water with a volume ratio of 1:4 and mechanically stirred at room temperature for 60 min to obtain a gallic acid mixed solution. Finally, the gallic acid mixed solution was added dropwise to the gelatin solution and mechanically stirred at 50 °C for 6 h. After the reaction was completed, the reaction solution was poured into a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed with deionized water for 7 days at a dialysis temperature of 35 °C. After the dialysis was completed, the gelatin grafted with gallic acid was obtained by filtration and freeze-drying.

[0032] (2) Add 12 g of poly (N-isopropylacrylamide) into 100 mL of deionized water and stir mechanically at 25 °C for 20 min to obtain a poly (N-isopropylacrylamide) solution. Then, add 3 g of gelatin grafted gallic acid and 0.8 g of poly (vinyl alcohol) with a relative molecular mass of 100,000 into 100 mL of deionized water and stir mechanically at 100 °C for 30 min and then at 25 °C for 20 min to obtain a mixed solution of gelatin grafted gallic acid and poly (vinyl alcohol). Finally, add the mixed solution of gelatin grafted gallic acid and poly (vinyl alcohol) dropwise into the poly (N-isopropylacrylamide) solution and stir mechanically at 25 °C for 20 min and then stand at 15 °C for 20 min to obtain a hydrogel.

[0033] Comparative Example 1 7.5 g of poly (N-isopropylacrylamide) was added to 70 mL of deionized water, and the mixture was mechanically stirred at 18 °C for 30 min to obtain a poly (N-isopropylacrylamide) solution. Then, 2 g of gallic acid and 0.6 g of poly (vinyl alcohol) with a relative molecular mass of 50,000 were added to 60 mL of deionized water, and the mixture was mechanically stirred at 80 °C for 45 min, and then allowed to stand at -15 °C for 30 min to obtain a mixed solution of gallic acid and poly (vinyl alcohol). Finally, the mixed solution of gallic acid and poly (vinyl alcohol) was added dropwise to the poly (N-isopropylacrylamide) solution, and the mixture was mechanically stirred at 5 °C for 30 min, and then allowed to stand at -15 °C for 15 min to obtain the finished product.

[0034] In this comparative example, gallic acid is used to replace gelatin to graft gallic acid to prepare a finished hydrogel. Because the molecular weight of gallic acid is significantly lower than that of gelatin, gallic acid can only be stably dispersed in the hydrogel system by polyvinyl alcohol through hydrogen bonding at a lower temperature. Therefore, in this comparative example, the stirring temperature and the standing temperature of gallic acid are reduced to below the relevant temperature of Example 1 to obtain a finished hydrogel with a phase transition temperature of 12.8°C. Figure 4 (B) is a morphology of the finished product prepared in this comparative example when it was left at 5°C for 15 days. The results show that obvious precipitation occurred when it was left at 5°C for 15 days, which indicates that the finished product prepared in this comparative example has poor storage stability. If the finished product prepared in this comparative example is left at 18°C, because 18°C ​​is higher than the phase transition temperature (12.8°C) of the finished product prepared in this comparative example, the finished product prepared in this comparative example will be transformed into a white solid hydrogel within 1 minute, that is, the finished product prepared in this comparative example is not suitable for storage at 18°C.

[0035] Comparative Example 2 7.5 g of poly (N-isopropylacrylamide) was added to 70 mL of deionized water, and the mixture was mechanically stirred at 18 °C for 30 min to obtain a poly (N-isopropylacrylamide) solution. Then, 2 g of gelatin with a relative molecular mass of 50,000 and 0.6 g of poly (vinyl alcohol) with a relative molecular mass of 50,000 were added to 60 mL of deionized water, and the mixture was mechanically stirred at 80 °C for 45 min and then at 18 °C for 30 min to obtain a mixed solution of gelatin and poly (vinyl alcohol). Finally, the mixed solution of gelatin and poly (vinyl alcohol) was added dropwise to the poly (N-isopropylacrylamide) solution, and the mixture was mechanically stirred at 18 °C for 30 min and then allowed to stand at 12 °C for 15 min to obtain a finished product.

[0036] Figure 5 (A) is a morphology picture of the finished product prepared in this comparative example at 18°C. The results show that it has obvious stratification phenomenon at 18°C, which indicates that the compatibility of gelatin and poly (N-isopropylacrylamide) is poor.

[0037] Comparative Example 3 7.5 g of poly (N-isopropylacrylamide) was added to 70 mL of deionized water, and the mixture was mechanically stirred at 18 °C for 30 min to obtain a poly (N-isopropylacrylamide) solution. Then, 1.5 g of gelatin with a relative molecular mass of 50,000, 0.5 g of gallic acid and 0.6 g of poly (vinyl alcohol) with a relative molecular mass of 50,000 were added to 60 mL of deionized water, and the mixture was mechanically stirred at 80 °C for 45 min and then at 18 °C for 30 min to obtain a mixed solution of gelatin, gallic acid and poly (vinyl alcohol). Finally, the mixed solution of gelatin, gallic acid and poly (vinyl alcohol) was added dropwise to the poly (N-isopropylacrylamide) solution, and the mixture was mechanically stirred at 18 °C for 30 min and then allowed to stand at 12 °C for 15 min to obtain the finished product.

[0038] Figure 5 (B) is a morphology of the finished product obtained in this comparative example at 18°C. The results show that it has obvious stratification phenomenon at 18°C, which means that simply adding gelatin and gallic acid without chemically bonding gelatin and gallic acid still has poor compatibility with poly (N-isopropylacrylamide).

[0039] Comparative Example 4 (1) 6 g of gelatin with a relative molecular mass of 50,000 was added to 200 mL of deionized water and mechanically stirred at 45 °C for 20 min to obtain a gelatin solution. Then, 2 g of gallic acid, 2.4 g of a mixture of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide (molar ratio of 1:2) were added to 200 mL of a mixed solution of N,N-dimethylformamide and deionized water with a volume ratio of 1:3 and mechanically stirred at room temperature for 45 min to obtain a gallic acid mixed solution. Finally, the gallic acid mixed solution was added dropwise to the gelatin solution and mechanically stirred at 40 °C for 12 h. After the reaction was completed, the reaction solution was poured into a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed with deionized water for 14 days at a dialysis temperature of 25 °C. After the dialysis was completed, the gelatin grafted with gallic acid was obtained by filtration and freeze-drying.

[0040] (2) Add 7.5 g of poly (N-isopropylacrylamide) into 70 mL of deionized water, and stir mechanically at 18 °C for 30 min to obtain a poly (N-isopropylacrylamide) solution. Then, add 2 g of gelatin-grafted gallic acid into 60 mL of deionized water, and stir mechanically at 80 °C for 45 min and then at 18 °C for 30 min to obtain a gelatin-grafted gallic acid solution. Finally, add the gelatin-grafted gallic acid solution drop by drop into the poly (N-isopropylacrylamide) solution, and stir mechanically at 18 °C for 30 min and then stand at 12 °C for 15 min to obtain the finished product.

[0041] The storage modulus, loss modulus and complex viscosity of the hydrogels prepared in three groups of embodiments and four groups of comparative examples were measured by a rotational rheometer during the heating process. As the test temperature increases, a phase transition occurs when the storage modulus of the hydrogel is greater than the loss modulus, and the temperature at this time is defined as the phase transition temperature. The white solid hydrogel is allowed to stand at 18 ° C for 1 h. When the white solid hydrogel is transformed into a transparent liquid hydrogel again, the hydrogel is judged to have phase transition reversibility. The transparent liquid hydrogel prepared in the embodiment is allowed to stand at 18 ° C until the transparent liquid hydrogel becomes turbid, and the standing time is used to characterize the storage validity period of the hydrogel prepared in the embodiment. The transparent liquid hydrogel prepared in the comparative example is allowed to stand at 5 ° C until the transparent liquid hydrogel becomes turbid, and the standing time is used to characterize the storage validity period of the hydrogel prepared in the comparative example. The freeze-dried hydrogel was immersed in PBS buffer with a pH of 7.4 and shaken at 37 °C for 15 days. After being taken out, it was repeatedly rinsed with deionized water, freeze-dried, and weighed. The degradability of the hydrogel was characterized by the weight loss rate of the freeze-dried hydrogel. The weight loss rate was calculated according to the following formula: Weight loss rate (%) = [(W0-W15) / W0]×100% Among them, W0 and W15 are the weights of freeze-dried hydrogel before and after degradation, respectively.

[0042] The performance test results are shown in Table 1.

[0043] Table 1 Performance test results

[0044] Comparative Example 1 uses gallic acid instead of gelatin to graft gallic acid. Although the finished product has thermosensitive phase transition reversibility, its phase transition temperature is low, the gel strength is low, and the storage stability is poor. Comparative Examples 2 and 3 show that whether gelatin is added alone or gelatin and gallic acid that are not chemically bonded are added, as long as gelatin and gallic acid are not chemically bonded, the obtained hydrogel will show obvious stratification. Comparative Example 4 does not add polyvinyl alcohol. Although the hydrogel will change from a transparent liquid to a white solid when the temperature is higher than the phase transition temperature, when the temperature is lowered below the phase transition temperature again, the white solid hydrogel cannot be converted into a transparent liquid hydrogel, which shows that the hydrogel obtained in Comparative Example 4 does not have thermosensitive phase transition reversibility. Because the phase transition temperature of the finished hydrogel obtained in Comparative Example 1 is only 12.8 ° C, the transparent liquid hydrogel obtained in Comparative Example 1 and Comparative Example 4 is left to stand at 5 ° C until the transparent liquid hydrogel becomes turbid, and the standing time is used to characterize the storage validity period of the hydrogel obtained in the comparative example. Theoretically, the lower the storage temperature, the better the storage stability of the thermosensitive phase change reversible hydrogel. Therefore, the test results in Table 1 can prove that the hydrogel prepared in the embodiment has better storage stability.

[0045] Therefore, it can be seen from the test results of the embodiments and comparative examples that a hydrogel having a high phase transition temperature and storage stability, good mechanical properties, excellent biocompatibility, thermosensitive phase transition properties and thermosensitive phase transition reversibility can be prepared by using poly (N-isopropylacrylamide) as a matrix, gelatin grafted gallic acid as an entangling agent, polyvinyl alcohol as a destructuring agent, and deionized water as a solvent through low-temperature stirring.

[0046] The above descriptions are merely embodiments of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention shall fall within the scope of the present invention.

Claims

1. A method for preparing a high-strength and high-storage-stability thermosensitive phase-change reversible hydrogel, characterized in that: The high-strength and high-storage-stability thermosensitive phase-change reversible hydrogel is prepared by low-temperature stirring with poly (N-isopropylacrylamide) as a matrix, gelatin grafted gallic acid as an entanglement agent, polyvinyl alcohol as a deconstruction agent, and deionized water as a solvent.

2. The preparation method according to claim 1, characterized in that: The following steps are involved: (1) Add 2-10 g of gelatin to 100-300 mL of deionized water, and stir mechanically at 30-60 °C for 10-30 min to obtain a gelatin solution. Then, add a mixture of gallic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide to a mixed solution of 100-300 mL of N,N-dimethylformamide and deionized water, and stir mechanically at room temperature for 30-60 min to obtain a gallic acid mixed solution. Finally, add the gallic acid mixed solution dropwise to the gelatin solution, and stir mechanically at 30-50 °C for 6-18 h. The reaction mixture is dialyzed, filtered, and freeze-dried to obtain gelatin grafted with gallic acid. (2) 3-12 g of poly (N-isopropylacrylamide) was added to 40-100 mL of deionized water, and the mixture was mechanically stirred at 10-25 °C for 20-40 min to obtain a poly (N-isopropylacrylamide) solution. Then, 1-3 g of gelatin grafted gallic acid and 0.4-0.8 g of poly (vinyl alcohol) were added to 20-100 mL of deionized water, and the mixture was mechanically stirred at 60-100 °C for 30-60 min, and then at 10-25 °C for 20-40 min to obtain a mixed solution of gelatin grafted gallic acid and poly (vinyl alcohol). Finally, the mixed solution of gelatin grafted gallic acid and poly (vinyl alcohol) was added dropwise to the poly (N-isopropylacrylamide) solution, and the mixture was mechanically stirred at 10-25 °C for 20-40 min, and then at 10-15 °C for 10-20 min to obtain the high-strength and high-storage-stability thermosensitive phase-change reversible hydrogel.

3. The preparation method according to claim 2, characterized in that: The relative molecular mass of the gelatin in step (1) is 10000-100000; the mass ratio of the gelatin to gallic acid is 2:1-4:1; the mass ratio of the mixture of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide to gallic acid is 1:1-1.5:1; and the molar ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide to N-hydroxysuccinimide is 1:

2.

4. The preparation method according to claim 2, characterized in that: The volume ratio of N,N-dimethylformamide to deionized water in step (1) is 1:2 to 1:

4.

5. The preparation method according to claim 2, characterized in that: The dialysis temperature in step (1) is 25-35°C, the time is 7-14 days, the molecular weight cut-off is 3500 Da, and the dialysate is deionized water.

6. The preparation method according to claim 2, characterized in that: The relative molecular mass of the polyvinyl alcohol in step (2) is 10000-100000.

7. A high-strength, high-storage-stability thermosensitive phase-change reversible hydrogel prepared by the method according to any one of claims 1 to 6, characterized in that: The phase transition temperature of the hydrogel is 32-33°C, the storage modulus at 37°C is 542-548 Pa, the composite viscosity at 5°C is 1.62-1.73 Pa·s, the composite viscosity at 37°C is 78.5-79.6 Pa·s, the storage validity period is greater than 365 days, and the weight loss rate is 68.4-71.7%.

Citation Information

Patent Citations

  • Preparation method of N-isopropyl acrylamide polymer / polyvinyl alcohol composite hydrogel and product thereof

    CN101608021A

  • Injectable medical temperature-sensitive hydrogel and preparation method thereof

    CN117467159A

  • Mechanically active hydrogel for treating intestinal fistula and preparation method thereof

    CN118903553A

  • A preparation method of temperature and ph sensitive hydrogel

    KR1020100086273A

  • A novel method to improve adhesive strength of reversible polymers and hydrogels

    WO2018232384A1

Cited By

  • Whitening type temperature indicator based on polyvinyl acetal polymer

    CN122149675A